SEBUAH META ANALISIS TENTANG PENGARUH SOFTWARE AKUNTANSI TERHADAP PERUSAHAAN - Nanda Vito; Agus Munandar (Universitas Kristen Krida Wacana, 2021)
The purpose of this analysis is to gain empirical data concerning the effect of what an Accounting Software has on the firms and users. The data that is used on this study consists of 7 research papers. In theory, digital software are meant to be a practical, easy to use, and efficient tool that can be used by a User. This Research will be done in the style of a meta-analysis. There are many benefits with using this method, such as already having existing research to be the main data set. With that fact in mind, we can use numerous papers as reliable sources to base this meta-analysis on. This analysis will contain numerous research papers concerning the effects of what an Accounting Software has on a firm. The results of this analysis show that Accounting Software have a positive impact on the efficiency and practicality of the accounting process, This is due to the basic purpose on why an accounting software was made in the first place, to help and simplify work for users. Keywords: Accounting Software, Accounting Programs, Accounting